How does the National Key Ecological Function Area policy affect the upgrading of the industrial structure?—based on the examination of the Yellow River Basin in China - Zhang, Yuqian; Luo, Huanqi; Su, Chenchen; Li, Yue; Xu, Chen; Wang, Huijuan (Frontiers in Environmental Science, 2024)
The transformation and upgrading of the industrial structure constitute a pivotal task for sustainable economic development, and the factors influencing this process are also of concern to developing countries around the world. Unfortunately, there is still relatively little systematic discussion on the impact of environmental policy on the industrial structure. Against this backdrop, we have employed the multi-period differences-in-differences (DID) model to assess the impact of the implementation of the National Key Ecological Function Area (NKEFA) policy on the industrial structure in the Yellow River Basin. Our findings reveal that this environmental policy fosters the advancement of industrial structure but does not influence its rationalisation. Regarding mediating effects, we confirm the positive impacts of population density and the investment in education. Furthermore, the policy effects are more pronounced in non-ethnic provinces with better basic conditions, whereas ethnic provinces exhibit almost no effect. The policy effects are more significant in large cities than in small and medium-sized cities. These findings enrich the existing exploration of the impact of environmental policy on industrial structure and provide a strong reference for policy practice in developing countries.